Plans, preferences or going with the flow: an online exploration of women's views and experiences of birth plans - Divall, Bernie; Spiby, Helen; Nolan, Mary; Slade, Pauline (Elsevier, 2017)
Objective To explore women’s views of birth plans, and experiences of their completion and use. Design A qualitative, exploratory study, using Internet-mediated research methods. Setting The discussion boards of two well-known, UK-based, online parenting forums, where a series of questions relating to birth plans were posted. Participants Members of the selected parenting forums who had written and used, or who had chosen not to write or use, a birth plan. Findings Women responded with a range of views and experiences relating to the completion and use of birth plans. The benefits of birth plans were described in terms of communication with healthcare professionals, potentially enhancing awareness of available options, and maintaining a sense of control during labour and birth. However, many respondents believed the idea of ‘planning’ birth was problematic, and described a reluctance to write a formal plan. The support of healthcare professionals, particularly midwives, was considered essential to the success of both writing and using birth plans. Key conclusions Our findings show a continued debate among women on the benefits and challenges involved in writing and using birth plans, suggesting problems for a ‘one size fits all’ approach often seen in the use of birth plan templates. In the context of maternity policy supporting women’s choice and personalised care, and as a way of acknowledging perceived problems of ‘planning’ for birth, a flexible approach to birth plans is required, including the consideration of employing alternative nomenclature. Implications for practice Birth plans remain a point of contention in care contexts around the world. Midwives and other healthcare providers play a central role in supporting women to discuss available options, whether or not they decide to complete a formal birth plan.